2019
DOI: 10.9734/ajee/2019/v9i430101
|View full text |Cite
|
Sign up to set email alerts
|

Social Impact of Odor Induced by Municipal Solid Waste Treatment Facilities in Ho Chi Minh City

Abstract: Landfills are mostly used to manage solid waste in Ho Chi Minh City, Vietnam. Due to inappropriate administration, there have been numerous issues over the years relating to odor and leachate. The purpose of this study is to explore the impact of odor stemming from Da Phuoc landfill site on surrounding areas. A questionnaire survey was administered through face-to-face interviews with 409 residents living in the affected areas. The findings of this study indicate that the odor perception of residents significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Nausea, shortness of breath, and feelings of unhappiness and depression were symptoms recorded in the population. Tran et al (2019) indicated that residents who live more than 5 km away from the MSW facility had severe odor annoyance from June to October and the period of time during which respondents perceived the worst odor is Figure 8. As shown in Figure 8, the majority of respondents perceived odor pollution during a period between 18:00-24:00, i.e., 6 pm to 12 am in the next day.…”
Section: Summary Of Community Survey Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nausea, shortness of breath, and feelings of unhappiness and depression were symptoms recorded in the population. Tran et al (2019) indicated that residents who live more than 5 km away from the MSW facility had severe odor annoyance from June to October and the period of time during which respondents perceived the worst odor is Figure 8. As shown in Figure 8, the majority of respondents perceived odor pollution during a period between 18:00-24:00, i.e., 6 pm to 12 am in the next day.…”
Section: Summary Of Community Survey Resultsmentioning
confidence: 99%
“…The first pattern is the high temperature in two separate seasons: the dry season between November and April, and the rainy season between May and October. The second pattern is the direction of the wind, which changes monthly: (i) from Jan to May in the South (S) or Southeast (SE) direction; (ii) from June to September in the West (W) or Southwest (SW) direction; (iii) from October to December in the Northeast (NE) direction (Tran et al, 2019). The windrose plot of the study area by each quarter for 2019 is shown in Figure 1.…”
Section: Climate Condition Of Survey Areamentioning
confidence: 99%
See 2 more Smart Citations